2019
DOI: 10.3390/plants8090300
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Oil of Thymbra capitata and its Application as A Biocide on Stone and Derived Surfaces

Abstract: Many chemicals used nowadays for the preservation of cultural heritage pose a risk to both human health and the environment. Thus, it is desirable to find new and eco-friendly biocides that can replace the synthetic ones. In this regard, plant essential oils represent effective alternatives to synthetic substances for the preservation of historical monuments. Thymbra capitata (syn. Thymus capitatus) is a medicinal and aromatic plant growing in the Mediterranean area and endowed with important pharmacological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 54 publications
(55 reference statements)
1
20
0
Order By: Relevance
“…Due to the presence of polyphenols, T. capitata EO is used in food preservation [ 31 ] and it has been demonstrated that it possesses antioxidant properties [ 32 ]. Moreover, the antimicrobial [ 33 , 34 ] and herbicidal activities [ 15 , 35 , 36 ] of T. capitata EO have been verified. Santolina chamaecyparissus L. (cotton lavender) is an aromatic plant belonging to Asteraceae family.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of polyphenols, T. capitata EO is used in food preservation [ 31 ] and it has been demonstrated that it possesses antioxidant properties [ 32 ]. Moreover, the antimicrobial [ 33 , 34 ] and herbicidal activities [ 15 , 35 , 36 ] of T. capitata EO have been verified. Santolina chamaecyparissus L. (cotton lavender) is an aromatic plant belonging to Asteraceae family.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies highlighted how EOs rich in phenolic compounds, such as thymol or carvacrol, have a strong antimicrobial activity. In particular, thymol seems to be bioactive against more than twelve different bacterial colonies [ 21 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thymus EO was selected due to its microbial properties, which have previously been reported in several studies [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. In particular, the Thymus vulgaris essential oil has been shown to be quite effective against several microorganisms [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thymbra capitata essential oil was proposed for use against cyanobacteria and green algae on historical monuments [86]. The major components of the essential oil were the phenolic monoterpene carvacrol (73.2%) and its biogenetic precursors γ-terpinene (6.9%) and p-cymene (4.3%).…”
Section: Biocidal Treatments With Compounds Of Natural Originmentioning
confidence: 99%